CHATGPT AND CRITICAL THINKING SKILLS IN HIGHER EDUCATION: AN OVERVIEW - Selvaraj, Bawani (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Artificial intelligence (AI) is transforming the teaching and learning paradigm and this shift opens up new possibilities in improving educational outcomes. As a widely adopted tool in higher learning institutions, Chat Generative Pre-Trained Transformer (ChatGPT) helps students engage with content, provide prompt feedback as well as create a learning environment that is interactive. This paper examines three underpinning theoretical frameworks: Scaffolding Theory, Cognitive Load Theory and Dual-Process Theory, in relation to the integration of ChatGPT in educational pursuits. Secondly, it discusses the impact of ChatGPT on students’ critical thinking skills in higher learning institutions. These aspects are often overlooked as previous research focus mainly on how ChatGPT enhances students’ academic performance and issues pertaining to academic integrity. Hence, this paper offers a cohesive viewpoint that illustrates the incorporation of technology and critical thinking skills in complementing students’ learning experiences. ChatGPT has the capacity to provide external assistance, manage limited cognitive resources and serve as facilitation strategy but in the same vein it could also inhibit the development of critical thinking skills. Thus, the use of AI in higher education remains a contested terrain and students need to be guided on how to use ChatGPT responsibly so that the academic standards are not compromised.